Criminal liability of the artificial intelligence - Олександр Едуардович Радутний (Проблеми Законності, 2017)
The article deals with the influence of robotics units on the life of modern mankind, the possibility of creating an artificial intelligence equal to the human intelligence or exceeding its level, the possibilities and validity of the recognition of artificial intelligence physically embodied in a robotics unit by an object and (or) subject of criminal legal relations, the relationship between information security and artificial intelligence research and its results.